The Influence of Perceived Usefulness and Cashback Reward Program Mediated by E-wallet Engagement on E-wallet User Satisfaction - Nurmalasari Nurmalasari; Nur Afifah; Mustaruddin Mustaruddin (Universitas Bina Sarana Informatika, 2025)
The rapid growth of digital payment systems makes e-wallets increasingly important in the financial technology sector. This study examines the effect of perceived usefulness and cashback reward programs on e-wallet user satisfaction, with e-wallet involvement as a mediating variable. The data collection techniques are observation of how users interact with e-wallet applications through usage analysis and monitoring of how often transactions are made, interviews with the aim of gaining in-depth insight into user experience and literature studies by collecting journals, articles related to this study. The data analysis uses the Structural Equation Modeling with Partial Least Squares (SEM-PLS) approach with SmartPLS 3.0, software following a two-stage approach: measurement model evaluation (outer model) and structural model evaluation (inner model). The measurement model assessment included convergent validity, discriminant validity, and reliability tests. The structural model evaluation examined path coefficients, significance levels, R-square values, and effect sizes.with data collected from 300 e-wallet users through purposive sampling.The population consisted of e-wallet users in Indonesia, with the sample selected using purposive sampling technique. The inclusion criteria required respondents to have used e-wallet applications for at least three months. The results indicate that perceived usefulness (β=0.137, p<0.05) and cashback reward programs (β=0.236, p<0.001) significantly influence e-wallet engagement. E-wallet engagement significantly affects user satisfaction (β=0.287, p<0.001), and perceived usefulness directly influences satisfaction (β=0.362, p<0.001). The mediation analysis reveals that e-wallet engagement partially mediates the relationship between both independent variables and user satisfaction. The findings suggest that e-wallet providers should focus on enhancing perceived usefulness and designing attractive reward programs while maintaining high user engagement to drive satisfaction.